Epidemiological aspects of visceral leishmaniasis in the municipality of Montes Claros-MG - Silva, Fernanda Santana da; Silva, Jefferson Oliveira; Aguiar, Matheus Felipe Ferreira; Santos Neto, João José Lopes dos; Rocha, Rogério Gonçalves da; Guimarães, Victor Hugo Dantas (Acta Scientiarum. Health Sciences, 2021)
Visceral leishmaniasis (VL), also known as ‘calazar’, is a serious chronic disease caused by Leishmania species from Leishmania (Leishmania) donovani complex, which the disease is characterized by abdominal swelling (hepatosplenomegaly) and may evolve to death in extreme cases. In this sense, the aim of our study was to assess the epidemiological profile of the cases found in Montes Claros (Minas Gerais state). A retrospective or cross-sectional study was carried out using secondary data provided by Health Information System (SINAN/HM) of Brazil from January 2010 to February 2020. Our data has shown that VL is an endemic disease in Montes Claros region, with 413 VL cases reported, 62.00% (252) male, average age ± standard deviation (years), and 93.46% (386) lived in Montes Claros city. The presence of comorbidities was observed in 13.70% (54) of the patients and in 7.26% (30). As for the evolution of the disease, 246 (59.56%) were cured, 30 (7.26%) died due to VL. Between 2010 and 2015, Glucantime® stands out, in which 46 (11.13%) patients used the drug, followed by common Amphotericin B 24 (13.48%) and liposomal Amphotericin B 38 (21.34%). In the period between 2016 and 2020, the most prevalent drug was liposomal Amphotericin B, with 71 (29.83%) patients using it, followed by Glucantime® 45 (18.9%). The condition evolved to death. We conclude that Montes Claros is still an endemic area for VL with an increased number of cases over time and a noticeable shift in patient profile towards children and young people. Joint efforts from different areas of scientific knowledge and public health services are needed to improve the effectiveness of visceral leishmaniasis surveillance and control actions. The population can contribute to this process of disease prevention and control, through educational actions in health and the environment.